2021
DOI: 10.1177/17534259211062553
|View full text |Cite
|
Sign up to set email alerts
|

Bergamottin alleviates LPS-induced acute lung injury by inducing SIRT1 and suppressing NF-κB

Abstract: Acute lung injury (ALI) is associated with a high mortality due to inflammatory cell infiltration and lung edema. The development of ALI commonly involves the activation of NF-κB. Since bergamottin is a natural furanocoumarin showing the ability to inhibit the activation of NF-κB, in this study we aimed to determine the effect of bergamottin on ALI. RAW264.7 mouse macrophages were pre-treated with bergamottin and then stimulated with LPS. Macrophage inflammatory responses were examined. Bergamottin (50 mg/kg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Bergamottin has been drawing increasing interest recently owing to its anti-inflammatory properties. It is reported that Bergamottin alleviates LPS-induced acute lung injury by inducing SIRT1 and inhibiting NF-κB ( An et al, 2021 ). Research also suggests that Bergamottin prevents LPS-induced endotoxic shock by modulating the NF-κB signaling pathway ( Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bergamottin has been drawing increasing interest recently owing to its anti-inflammatory properties. It is reported that Bergamottin alleviates LPS-induced acute lung injury by inducing SIRT1 and inhibiting NF-κB ( An et al, 2021 ). Research also suggests that Bergamottin prevents LPS-induced endotoxic shock by modulating the NF-κB signaling pathway ( Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The protein concentration and the inflammatory cell number of BALF in the P5 group increased by 3.32-fold and 4.66-fold, respectively, compared to the untreated group. Typical features of ALI are the alveolar accumulation of protein-rich fluid and activated immune cells due to pulmonary endothelial barrier disruption and increased vascular permeability [ 38 , 39 ]. The results indicate that GF-17 can induce inflammatory reactions in the lungs, leading to inflammatory injury in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we found LPS can promote the secretion of TNF-α, IL-1β, and IL-6 while safflor yellow A could mitigate the excessive synthesis of these cytokines, which indicated its anti-inflammatory effects in Beas-2B cells. More experimental evidences have disclosed activation of NF-κB signaling pathway was involved in ALI/ARDS (Cao et al 2018 ; An et al 2021 ), which could regulate the secretion of these pro-inflammatory cytokines in transcription (Hayden and Ghosh 2011 ). Under unstressed conditions, NF-κB dimers are bound to IκBα to form the complex and sequestered in cytosol (Oeckinghaus et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%